Iterative hard thresholding based impulsive noise suppression method in power line communication system - Mingchen YU; Youming LI; Caimei FU; Guili ZHOU (Dianxin kexue)
The performance of power line communication systems is seriously affected by impulsive noise.The compressed sensing theory has been applied for estimation in view of the sparse property of impulsive noise in the time domain.A compressed sensing method based on the iterative hard thresholding was proposed to estimate the impulsive noise.Firstly,the thresholding value was updatedby iteration,and then the thresholding function was used to estimate the impulsive noise.Finally,the impulsive noise was cancelled by subtracting the estimation value from the received signal.Simulation results show that the proposed method can efficiently estimate the impulsive noise and promote the performance bothinmean square error and signal to noise ratio.